2020
DOI: 10.12998/wjcc.v8.i14.2988
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic retrograde cholangiopancreatography in elderly patients: Difficult cannulation and adverse events

Abstract: BACKGROUND Endoscopic retrograde cholangiopancreatography (ERCP) is a valuable therapeutic technique for pancreatobiliary diseases, and its application in the elderly is no longer limited. However, a higher incidence of procedure difficulty and periprocedural adverse events might be expected in elderly patients due to the presence of other medical disorders and the poor general condition of this population. AIM To evaluate the incidence, causes, and management of diffic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
2
11
1
Order By: Relevance
“…In another study conducted on difficult cannulation, 42.1% of the maneuvers used were pancreatic guidewire and 26.8% were pancreatic stents. The frequency rates of using these maneuvers are similar to the data obtained in our study (22). The frequency of maneuvers used in difficult biliary cannulation cases was similar in both patient groups.…”
Section: Definitions and Criteriasupporting
confidence: 87%
“…In another study conducted on difficult cannulation, 42.1% of the maneuvers used were pancreatic guidewire and 26.8% were pancreatic stents. The frequency rates of using these maneuvers are similar to the data obtained in our study (22). The frequency of maneuvers used in difficult biliary cannulation cases was similar in both patient groups.…”
Section: Definitions and Criteriasupporting
confidence: 87%
“…However, there is evidence that age itself is not the determinant of inferior outcomes in elective and emergency biliary diseases[ 10 , 11 ]. Endoscopic retrograde cholangiopancreatography (ERCP) have been demonstrated to be safe with good outcomes in elderly patients[ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is evidence that age itself is not the determinant of inferior outcomes in elective and emergency biliary diseases[ 10 , 11 ]. Endoscopic retrograde cholangiopancreatography (ERCP) have been demonstrated to be safe with good outcomes in elderly patients[ 11 , 12 ]. In a study including 149 acute cholecystitis patients treated with emergency laparoscopic cholecystectomy (LC), Amirthalingam et al [ 13 ] showed that patient comorbidities and not age determine outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies showed that the PEP rate of TPS is similar to other advanced cannulation methods; even NKP could be better to avoid PEP 17 , 19 , 20 . However, limited studies have prospectively compared PEP rate in TPS and NKP, in addition to a lack of information on using uniform PEP preventive methods, which could make the PEP rate with TPS even lower 5 , 17 .…”
Section: Discussionmentioning
confidence: 96%